Vitrectomy with internal limiting membrane peeling versus its flap insertion for macular hole in high myopia: a Meta-analysis - Ya-Jun Wu; Jie Rao; Kang-Rui Wu; Na Wu; Yi Cheng; Xiao-Xuan Xu; Li Yan; Yi Shao; Yu Tian; Xiao-Rong Wu (International Journal of Ophthalmology, 2020)
AIM: To compare the anatomic and functional outcomes between vitrectomy with internal limiting membrane (ILM) peeling and internal ILM flap insertion technique for high myopia macular hole (MH). METHODS: PubMed, Cochrane Library, EMBASE, and CNKI were systematically searched, and all studies involved MH were included. The closure rate of MH and the postoperative best-corrected visual acuity (BCVA) at 6mo after the initial surgery were the primary measures. All statistical tests were performed in Review Manager 5.3. RESULTS: Five studies that included 151 eyes of 151 patients were finally included, all of which were retrospectively comparative studies. Between the pars plana vitrectomy (PPV) with ILM peeling surgery and the ILM insertion technique, the latter had significantly better efficacy with respect to the closure rate of MH (OR=21.32, 95%CI=7.25-62.67, P<0.001); However, regarding BCVA at 6mo after the initial surgery in MH, there was no statistical significance between the groups (OR=-0.04, 95%CI=-0.22-0.14, P=0.66). In addition, regarding the rate of retinal reattachment after the initial surgery, the two different methods were not significantly different (OR=2.22, 95%CI=0.34-14.32, P=0.4). CONCLUSION: Both ILM peeling and ILM insertion technique could significantly improve anatomic outcomes of MH in high myopia with or without retinal detachment (RD), and anatomic outcomes are more effective. However, there is no statistical significance in BCVA at 6mo after the initial surgery in MH, or in the rate of retinal reattachment after the first surgery, between the two methods.